1979
DOI: 10.1161/01.cir.59.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cholesterol-lowering diet on mortality from coronary heart disease and other causes.

Abstract: International statistics indicate that there is a close correlation between the consumption of saturated fats (dairy fats and meat fats) and the mortality from coronary heart disease (CHD), and this conception has been confirmed by many epidemiological studies. Such studies alone, however, cannot prove the existence of a cause-and-effect relationship between these two variables; dietary intervention trials are needed. The Finnish Mental Hospital Study was such a trial, conducted in two hospitals near Helsinki … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0
6

Year Published

1981
1981
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(60 citation statements)
references
References 14 publications
0
54
0
6
Order By: Relevance
“…Nutrition-related epidemiological associations have shown significant direct correlations between dairy fat consumption and cardiovascular outcomes (Turpeinen, 1979;Renaud & de Lorgeril, 1989;Artaud-Wild et al, 1993). Of particular interest are the comments regarding cheese that appear to differentiate its effect on plasma cholesterol from other high-fat dairy foods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nutrition-related epidemiological associations have shown significant direct correlations between dairy fat consumption and cardiovascular outcomes (Turpeinen, 1979;Renaud & de Lorgeril, 1989;Artaud-Wild et al, 1993). Of particular interest are the comments regarding cheese that appear to differentiate its effect on plasma cholesterol from other high-fat dairy foods.…”
Section: Discussionmentioning
confidence: 99%
“…The epidemiological association between national consumption of butter fat and cardiovascular mortality has been advanced as a key reason for reducing intake of full-cream dairy fat (Artaud-Wild et al, 1993). Earlier Turpeinen (1979) had also demonstrated a strong correlation (r ¼ 0.75) between dairy fat consumption in 22 countries and mortality from coronary heart disease (CHD). However, the possibility that not all full-cream fat dairy products influence plasma cholesterol identically has been rarely investigated.…”
Section: Introductionmentioning
confidence: 99%
“…All these studies indicated that a few factors-notably smoking, elevated serum cholesterol, and elevated blood pressure-predict a major part of subsequent CHD risk, inde pendent of other potential factor studied. Results from basic biochemical studies, as well as results from a few experimental and quasi-experimental studies on the different risk factors, have also long been available: for smoking cessation (8), for cholesterol-lowering diets (62), and for blood pressure treatment (63).…”
Section: The Medical and Epidemiological Frameworkmentioning
confidence: 99%
“…Coronary heart disease (CHD) is a major cause of morbidity and mortality worldwide. Epidemiological, genetic, laboratory animal and metabolic ward studies have provided evidence linking high blood cholesterol with atherosclerosis and CHD [23] [24]. While cholesterol is believed to be chiefly implicated in the relationship, serum triacylglycerols may also play a role [25].…”
Section: Discussionmentioning
confidence: 99%